Heterogeneous face recognition over cross-distance & cross-spectrum - Miao, Lin (2014)
This report concluded the final year project, which spread over the whole academic year, as part of the academic requirements of the School of Electrical and Electronics Engineering. It encompassed the project introduction, experiments performed, results obtained, as well as future development of the project.